2019
DOI: 10.1002/rcm.8453
|View full text |Cite
|
Sign up to set email alerts
|

Practical and theoretical considerations for the determination of δ13CVPDB values of methylmercury in the environment

Abstract: Rationale: Analytical methods that can identify the source and fate of mercury and organomercury compounds are likely to be useful tools to investigate mercury in the environment. Carbon isotope ratio analysis of methylmercury (MeHg) together with mercury isotope ratios may offer a robust tool to study environmental cycling of organomercury compounds within fish tissues and other matrices.Methods: MeHg carbon isotope ratios were determined by gas chromatography/ combustion-isotope ratio mass spectrometry (GC/C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…13 Several laboratories have tried to redetermine the absolute carbon isotope ratio R 13/12 of VPDB. [14][15][16][17][18][19][20][21][22] Malinovsky et al 22 gave an overview of reported values. Currently, the recommended value of R 13/12,VPDB (ref.…”
Section: Introductionmentioning
confidence: 99%
“…13 Several laboratories have tried to redetermine the absolute carbon isotope ratio R 13/12 of VPDB. [14][15][16][17][18][19][20][21][22] Malinovsky et al 22 gave an overview of reported values. Currently, the recommended value of R 13/12,VPDB (ref.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, if several RMs have been characterised against the same subset of existing RMs, their assigned isotope delta values will all be correlated. Without a clear picture of the calibration hierarchy, it is difficult to establish the degree to which the assigned values of RMs are correlated and to include this correlation factor within an uncertainty budget . Neglecting to account for this correlation results in an incomplete uncertainty budget as the correlation factor is unknown.…”
mentioning
confidence: 99%